Signal processing for multiple receive antenna systems in the presence of multiple access interference - Salam, Naser (University of Ottawa (Canada), 2004)
In wireless communications systems employing DS-CDMA, the base stations with multiple antennas receive signals from different mobiles that are affected by fading and noise as well as interference from other users, thus diminishing the capacity. This dissertation considers a base station with multiple receive antennas which are weighted spatially by using maximal ratio combining. Moreover, at the transmitter side, the thesis examines the use of pilot signals along with the data stream for channel estimation purpose. For each user, the pilot signals are transmitted in parallel with the data signal using orthogonal signature waveforms to those of the data signal. The proposed receiver in this thesis uses a decorrelator detector to not only to decorrelate the data signal from the MAI components, but also to decorrelate the pilot signal to achieve good channel gain estimation. The study shows that the proposed system has a good resistance toward the near-far problem, give good space receiver performance efficiency comparing it with conventional space receivers and it has Less power assigned to the pilot power stream to obtain best channel estimation within a certain fading rate.
Keywords: Engineering, Electronics and Electrical.